PENGARUH CENTRALIZATION TERHADAP INTELLECTUAL CAPITAL MELALUI IMPLEMENTASI ERP SEBAGAI VARIABEL MEDIASI - Aloysius Richard Anthony; Priskila Adiasih; Saarce Elsye Hatane (Business Accounting Review, 2017)
The aim of this study was to determine whether there was influence of centralization to intellectual capital through ERP implementation as the mediating variable. The population used in this study was companies in Indonesia that implements ERP system. The sample of this research was 36 companies in Indonesia that have implemented ERP system.Data analysis techniques used in this research was partial least square to describe the relationships among variables. The data processed by using WarpPLS 5.0. The results showed that centralization with ERP implementation had significant affect on intellectual capital in companies that implement ERP system in Indonesia.